A phase II study of continuous oral mTOR inhibitor everolimus for recurrent, radiographic-progressive neurofibromatosis type 1–associated pediatric low-grade glioma: a Neurofibromatosis Clinical Trials Consortium study. Issue 10 (1st April 2020) - Ullrich, Nicole J; Prabhu, Sanjay P; Reddy, Alyssa T; Fisher, Michael J; Packer, Roger; Goldman, Stewart; Robison, Nathan J; Gutmann, David H; Viskochil, David H; Allen, Jeffrey C; Korf, Bruce; Cantor, Alan; et al.
Abstract: Background: Activation of the mammalian target of rapamycin (mTOR) pathway is observed in neurofibromatosis type 1 (NF1) associated low-grade gliomas (LGGs), but agents that inhibit this pathway, including mTOR inhibitors, have not been studied in this population. We evaluate the efficacy of the orally administered mTOR inhibitor everolimus for radiographically progressive NF1-associated pediatric LGGs. Methods: Children with radiologic-progressive, NF1-associated LGG and prior treatment with a carboplatin-containing chemotherapy were prospectively enrolled on this phase II clinical trial to receive daily everolimus. Whole blood was analyzed for everolimus and markers of phosphatidylinositol-3 kinase (PI3K)/mTOR pathway inhibition. Serial MRIs were obtained during treatment. The primary endpoint was progression-free survival at 48 weeks. Results: Twenty-three participants (median age, 9.4 y; range, 3.2–21.6 y) were enrolled. All participants were initially evaluable for response; 1 patient was removed from study after development of a malignant peripheral nerve sheath tumor. Fifteen of 22 participants (68%) demonstrated a response, defined as either shrinkage (1 complete response, 2 partial response) or arrest of tumor growth (12 stable disease). Of these, 10/15 remained free of progression (median follow-up, 33 mo). All remaining 22 participants were alive at completion of therapy. Treatment was well tolerated; no patient discontinued therapy due to toxicity. Pharmacokinetic parameters and pre-dose concentrations showed substantial between-subject variability. PI3K/mTOR pathway inhibition markers demonstrating blood mononuclear cell mTOR pathway inactivation was achieved in most participants. Conclusion: Individuals with recurrent/progressive NF1-associated LGG demonstrate significant disease stability/shrinkage during treatment with oral everolimus with a well-tolerated toxicity profile. Everolimus is well suited for future consideration as upfront or combination therapy in this patient population.